Low-frequency vibration therapy enhances recovery in college football athletes after fatigue-induced exercise - Zhao, Wenlong; Eungpinichpong, Wichai; Wang, Xingze (International Journal of Public Health Science (IJPHS), 2024)
Vibration therapy is known to help with muscle fatigue from daily activities. Research is ongoing, but early signs suggest it might be a promising tool for health promotion via faster recovery after streneous exercise. This randomized controlled trial examined the effects of low-frequency vibration therapy (LFVT) on recovery of lower back muscles after induced fatigue. Recovery-related parameters, including pressure pain threshold (PPT), visual analog scales (VAS) of perceived fatigue, sit-and-reach (SAR), and heart rate variability (HRV) were measured before the session of induced fatigue, immediately after receiving either the LFVT or the rest, and 24-hour follow-up period. Seventy participants were allocated to either LFVT group (received a 10-minute session of LFVT) or control group (rested under the same environment). Results showed that participants in LFVT group significantly improved VAS and PPT after intervention. The between-group comparison revealed that the improvement in the average heartbeat (AHB), VAS, SAR, and PPT were greater in LFVT group than in control group immediately after the treatment. Moreover, improvements in SAR and PPT were also greater in the LFVT group than in the control at 24-hour follow-up. The findings revealed that LFVT can be used as a recovery-health care method for football athletes.